The nigger of the "Narcissus" a tale of the sea - Conrad, Joseph 1857-1924 (The world's classics, 1984)
This account of the voyage of a sailing ship from Bombay harbour to the Port of London explores the psychological pressures on a group of nineteenth century seamen as they face the extemes of nature and the secrets and evasions of two of their comrades.